Game Edukasi Siswa SLB Untuk Meningkatkan Literasi Matematika Berbasis Android - Hasanuddin, Muhammad Hasrul; Indra Syahyadi, Asep; Darmatasia, Darmatasia; Ridwang, Ridwang (Prodi Sistem Informasi UIN Alauddin, 2023)
The research aims to develop and test the effectiveness of an Android-based educational game designed specifically for students of the Extraordinary School (SLB) in improving their mathematical literacy. Mathematical literacy is an essential skill that supports an individual's ability to understand, analyze, and apply mathematical concepts in everyday life. However, SLB students often face the challenge of acquiring a sufficient understanding of mathematics due to various barriers in their learning. This research methodology covers the stages of development of educational games designed in accordance with the characteristics of SLB students and the principles of effective mathematical learning. After the game was developed, the study involved a group of SLB students in a field experiment using a quasi-experimental approach with the control group. During a certain period, students from the experimental group participated in learning sessions using educational games, while students from control groups received conventional mathematical learning. The results of this study are expected to provide insight into the extent to which this Android-based educational game is effective in improving the mathematical literacy of SLB students. Furthermore, the research also has the potential to provide valuable input for further development of similar educational games that can be used as an inclusive learning tool for students with special educational needs. Increased mathematical literacy among SLB students can provide long-term benefits in preparing them to face the demands of mathematics in their later lives